Phase-transfer induced room temperature ferromagnetic behavior in 1T@2H-MoSe(2) nanosheets - Xia, Baorui (Sci Rep, 2017)
Manipulating electronic and magnetic properties of two-dimensional transitional-metal dichalcogenides has raised a lot of attention recently. Herein we report the synthesis and ferromagnetic properties of phase-transfer induced room temperature ferromagnetic behavior in 1 T@2H-MoSe(2) nanosheets. Experimental results indicate the saturated magnetization of the 1 T@2H-MoSe(2) compound increases first and then decreases as the increasing of 1 T-MoSe(2) phase, where 65.58% 1 T-MoSe(2) phase incorporation in 2H-MoSe(2) could enhance the saturated magnetization from 0.32 memu/g to 8.36 memu/g. Besides, obvious magnetoresistance behaviors are observed in these samples, revealing their potential applications in future spintronics.